Advances and highlights in T and B cell responses to drug antigens - Fernández-Santamaría, Rubén; Ariza Veguillas, Adriana; Fernández-Duarte, Tahía Diana; Céspedes Lagos, José Antonio; Labella, Marina; Mayorga Mayorga, Cristobalina; Torres-Jaén, María Josefa (Wiley, 2021)
The immunological mechanisms involved in drug hypersensitivity reactions (DHRs) are complex, and despite important advances, multiple aspects remain poorly understood. These not fully known aspects are mainly related to the factors that drive towards either a tolerant or a hypersensitivity response and specifically regarding the role of B and T cells. In this review, we focus on recent findings on this knowledge area within the last 2 years. We highlight new evidences of covalent and non-covalent interactions of drug antigen with proteins, as well as the very first characterization of naturally processed flucloxacillin-haptenated human leukocyte antigen (HLA) ligands. Moreover, we have analysed new insights into the identification of risk factors associated with the development of DHRs, such as the role of oxidative metabolism of drugs in the activation of the immune system and the discovery of new associations between DHRs and HLA variants. Finally, evidence of IgG-mediated anaphylaxis in humans and the involvement of specific subpopulations of effector cells associated with different clinical entities are also topics explored in this review. All these recent findings are relevant for the underlying pathology mechanisms and advance the field towards a more precise diagnosis, management and treatment approach for DHRs.
Keywords: Inmunología; B cell; Basic immunology; Drug allergy; T cell